The adventure of a third way: Motion events in Mandarin. (May 2021) - Wen, Xu; Shan, Xinxin
Abstract : Drawing on Talmy's analysis of lexicalization patterns (1985, 1991, 2000) and Slobin's "Thinking for Speaking" hypothesis (1991, 1996a, 2000), we examined the linguistic characteristics of habitual descriptions of motion events in Mandarin and found that the structural and discourse characteristics of Mandarin exhibited patterns that were not entirely the same as those of either Satellite-framed languages or Verb-framed languages but showed instead hybrid patterns. The results were in turn applied to a set of properties proposed by Talmy (2005, 2016) for identifying the main verb status in a construction. The analysis reveals that Equipollent framing holds a dominant position in Mandarin. Highlights: Mandarin displays a hybrid pattern in the coding of motion events in its spoken discourse. Mandarin speakers make frequent use of serial verb constructions to describe motion events. "Manner + Verb serial constructions" in Mandarin can be categorized into three subtypes. Equipollent framing holds a dominant position in Mandarin.